Anabolic steroids use Is associated with impairments in atrial and ventricular cardiac structure and performance in athletes - Grandperrin, A.; Schuster, I.; Moronval, P.; Izem, O.; Rupp, T.; Obert, P.; Nottin, S. (Medicine & Science in Sports & Exercise, 2022)
Purpose Despite potential severe cardiac side effects, anabolic androgenic steroids (AAS) are increasingly used by strength athletes. However, previous echocardiographic studies focused on the left ventricular (LV) strains but did not assess LV twist and untwist mechanics. Moreover, left atrial (LA) function has been often neglected, and its stiffness, an important determinant of LA reservoir function, has never been challenged. The aim of this study was to investigate the effects of AAS on LA and LV morphologies and functions in strength athletes.